PRIDE Review 1996 - McAdoo, Robert S.; Wilhem, Beverly D. (My University, 1996)
Summary of the 1996 actiivities of the Kansas PRIDE program and affiliated communities.
Keywords: Administrative and Research Reports; Community Development